Mycobacterium tuberculosis Triggers Apoptosis in Peripheral Neutrophils Involving Toll-Like Receptor 2 and p38 Mitogen Protein Kinase in Tuberculosis Patients - Alemán, Mercedes (Infect Immun, 2004)
Polymorphonuclear neutrophils (PMN) exposed to Mycobacterium tuberculosis display bactericidal responses and produce inflammatory proteins. This PMN-mediated inflammatory response is regulated by an activation of the apoptotic program, which collaborates to avoid tissue injury. In vitro, circulating PMN from patients with tuberculosis (TB) show an increased spontaneous apoptosis, and M. tuberculosis-induced activation accelerates the PMN apoptosis. In this study, we evaluated the mechanisms involved in spontaneous and M. tuberculosis-induced apoptosis. We demonstrate that apoptosis of PMN is not induced by lipoarabinomannan or by a whole-cell lysate of M. tuberculosis and that neither tumor necrosis factor alpha nor CD11b, CD14, and Fcγ receptors are involved. Apoptosis of PMN from patients with active TB (TB-PMN) is induced by the interaction with the whole M. tuberculosis via Toll-like receptor 2 (TLR2), and, in contrast to spontaneous apoptosis, it involves the p38 mitogen-activated protein kinase (MAPK) pathway. These results correlate with a high expression of phosphorylated p38 (p-p38) in circulating TB-PMN and with the ability of M. tuberculosis to induce in vitro the expression of p-p38 in PMN. Therefore, when the bacterial burden is low, TB-PMN could be detecting nonopsonized M. tuberculosis via TLR2, leading to the activation of the p38 MAPK pathway, which in turn would induce PMN activation and apoptosis. This mechanism needs further confirmation at the site of infection.